Association of cord blood vitamin D and genetic polymorphisms with childhood food allergy in Shanghai, China: a prospective cohort - Wang, Xirui; Cai, Yingying; Pei, Jingjing; Wang, Bin; Tian, Ying; Zhang, Jun; Yu, Xiaodan (Frontiers in Nutrition, 2025)
BackgroundEmerging evidence suggests vitamin D plays a dual role in immune regulation, yet its interplay with genetic susceptibility in early-life allergy development remains poorly understood. This prospective cohort study investigated whether cord blood 25-hydroxyvitamin D [25(OH)D] levels interact with immunoregulatory gene variants to influence childhood food allergy risk.MethodsA total of 1,049 mother-infant pairs from the Shanghai Allergy Cohort were stratified by cord blood 25(OH)D concentrations (<15, 15–25, >25 ng/mL). Food allergy diagnoses at 6, 12, and 24 months followed standardized clinical criteria. Five single-nucleotide polymorphisms (SNPs) (IL4, IL4R, IL13, MS4A2) were genotyped using MALDI-TOF MS. Multivariable logistic regression evaluated associations between vitamin D, genetic polymorphisms, and allergy outcomes, adjusting for birth season, maternal allergy history, and environmental confounders. Gene-vitamin D interactions were tested via stratified analyses.ResultsA U-shaped relationship was observed between cord blood serum25(OH)D levels and the risk of developing childhood food allergies. Both deficient (<15 ng/mL) and elevated (>25 ng/mL) 25(OH)D levels at birth independently increased 6-month food allergy risk (adjusted OR = 2.55 and 2.38, respectively). By 24 months, only deficient levels showed attenuated effects (OR = 1.14, p = 0.779). IL4R rs1801275 AA, IL13 rs20541 GG, and IL-4 rs2243250 CC genotypes synergistically amplified allergy risk under vitamin D deficiency (adjusted OR = 26.14, p = 0.019; OR = 6.51, p = 0.025; OR = 4.13, p = 0.007). Notably, the protective effect of MS4A2 rs569108 GG genotype observed at reference vitamin D levels (adjusted OR = 0.55, p = 0.016) was attenuated at high levels (OR = 0.68, p = 0.149).ConclusionGenetic susceptibility in Th2 pathway genes (IL4R, IL-4, IL13) dramatically amplified food allergy risk under vitamin D deficiency, with AA/GG/CC genotypes conferring 4- to 26-fold increased susceptibility. Conversely, the protective effect of MS4A2 rs569108 GG genotype was compromised at high vitamin D levels (>25 ng/mL). Our findings underscore that personalized vitamin D thresholds during pregnancy must account for fetal genetic background to mitigate allergy risk.